ON SOME SINGULAR INTEGRAL EQUATIONS ON THE SEMI-AXIS - Simonyan, V.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
In this paper the non-characteristic singular integral equations on the semi-axis are discussed. The solution of these equations is reduced to the solution of one-dimensional pseudo-differential equations. Some examples of singular equations for which explicit solutions exist are provided.